Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1101/2023.07.18.549489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription regulates the spatio-temporal dynamics of genes through micro-compartmentalization

Abstract: Although our understanding of the involvement of heterochromatin architectural factors in shaping nuclear organization is improving, there is still ongoing debate regarding the role of active genes in this process. In this study, we utilize publicly-available Micro-C data from mouse embryonic stem cells to investigate the relationship between gene transcription and 3D gene folding. Our analysis uncovers a nonmonotonic - globally positive - correlation between intragenic contact density and Pol II occupancy, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
(249 reference statements)
1
1
0
Order By: Relevance
“…Pol 2 occupancy appears as a key determinant of gene folding through phase separation. Interestingly, the speaker suggested that Pol 2-mediated condensation, coupled with transcriptional bursting, may slow down gene mobility, aligning with Bystricky’s observations [ 27 ].…”
Section: And Everything Is Movingsupporting
confidence: 66%
“…Pol 2 occupancy appears as a key determinant of gene folding through phase separation. Interestingly, the speaker suggested that Pol 2-mediated condensation, coupled with transcriptional bursting, may slow down gene mobility, aligning with Bystricky’s observations [ 27 ].…”
Section: And Everything Is Movingsupporting
confidence: 66%
“…One-sided halt or pause of loop-extrusion leads to the emergence of stripes in interaction heatmaps 13,35 . It is demonstrated that the strength of stripe features correlates with transcription rates and RNAPII occupancy at promoters 1,48 . Here, we demonstrate that the H3K27me3-marked promoters that are depleted for RNAPII display stripe formation in mESC.…”
Section: Discussionmentioning
confidence: 99%